SEXUAL VIOLENCE AGAINST GIRLS AND ADOLESCENTS - Guevara Ríos, Enrique (2024)
Sexual violence against girls and adolescents in Peru represents a public health crisis with profound physical, psychological, and social repercussions. Despite the alarming figures, gaps in access to health services and justice perpetuate the vulnerability of victims. This editorial seeks to highlight the magnitude of the problem, its determinants, and its impact on maternal and child health, highlighting the urgency of strengthening prevention strategies, comprehensive care, and evidence-based public policies. Ensuring a multidisciplinary approach centered on human rights is key to mitigating this problem and protecting the most vulnerable populations.